Wafer-Scale Epitaxial Growth of Unidirectional WS 2 Monolayers on Sapphire - Chubarov, Mikhail; Choudhury, Tanushree H.; Hickey, Danielle Reifsnyder; Bachu, Saiphaneendra; Zhang, Tianyi; Sebastian, Amritanand; Bansal, Anushka; Zhu, Haoyue; Trainor, Nicholas; Das, Saptarshi; Terrones, Mauricio; Alem, Nasim; et al. (ACS nano, 2021)
Realization of wafer-scale single-crystal films of transition metal dichalcogenides (TMDs) such as WS requires epitaxial growth and coalescence of oriented domains to form a continuous monolayer. The domains must be oriented in the same crystallographic direction on the substrate to inhibit the formation of inversion domain boundaries (IDBs), which are a common feature of layered chalcogenides. Here we demonstrate fully coalesced unidirectional WS monolayers on 2 in. diameter -plane sapphire by metalorganic chemical vapor deposition using a multistep growth process to achieve epitaxial WS monolayers with low in-plane rotational twist (0.09°). Transmission electron microscopy analysis reveals that the WS monolayers are largely free of IDBs but instead have translational boundaries that arise when WS domains with slightly offset lattices merge together. By regulating the monolayer growth rate, the density of translational boundaries and bilayer coverage were significantly reduced. The unidirectional orientation of domains is attributed to the presence of steps on the sapphire surface coupled with growth conditions that promote surface diffusion, lateral domain growth, and coalescence while preserving the aligned domain structure. The transferred WS monolayers show neutral and charged exciton emission at 80 K with negligible defect-related luminescence. Back-gated WS field effect transistors exhibited an / of ∼10 and mobility of 16 cm /(V s). The results demonstrate the potential of achieving wafer-scale TMD monolayers free of inversion domains with properties approaching those of exfoliated flakes.